CLINICAL APPLICATIONS OF ELASTOGRAPHY: AN OVERVIEW - SATYANAND TYAGI; SACHIN KUMAR (International Journal of Pharma and Bio Sciences, 2010)
Elastography is a non-invasive medical imaging technique that detects tumors based on their stiffness (elasticity) compared to normal tissue. The most common type of elastography uses ultrasonic imaging to compare the shapes of the tissue under examination before and after it is compressed slightly. Cancerous tumors tend to be many times stiffer than normal tissue, which "gives" under compression. An image in which different degrees of stiffness show as different shades of light and dark is called an elastogram. Many tumors, including breast tumors, show up better in an elastogram than in conventional ultrasonic images. Elastography has been studied in the laboratory since the mid-1990s. It is now being considered as a possible substitute for a breast biopsy, which is an invasive surgical procedure that removes a sample of tissue for pathological examination. The aim of present article is to provide in depth knowledge about clinical applications of elastography technique in current medical scenario.